Integrasi Pendidikan Karakter Dalam Pembelajaran Kimia Materi Minyak Bumi Pada Siswa Kelas XI MIPA SMA Negeri 5 Palangka Raya - Seliwati Seliwati (Jurnal Ilmiah Kanderang Tingang, 2021)
Character education will be the basis in the formation of nation-quality character.The Indonesian nation is currently facing the problem of the character of the nation's next generation. Therefore the 2013 curriculum emphasizes the importance of character education. SMA Negeri 5 Palangka Raya has established character education to produce students who have superior personalities who not only have cognitive abilities but have characters that are able to realize success. This study aims to describe the integration of character education in the learning of petroleum materi chemistry in class XI MIPA SMA Negeri 5 Palangka Raya 2019/2020 school year. Integrasi of character education in the learning process of petroleum material chemistry is carried aut starting from the planning, implementation, and evaluation stages. Character are: 1) be grateful, 2) honest, 3) discipline, 4) collaboration, 5) creative, 6) environmental care, and 7) responsible. The research method used is descriptive method with the research subjects 144 students of class XI MIPA SMA Negeri 5 Palangka Raya. Data gainet through observation assessment by teachers, self-assessment and peer assessment. The predicate and average character score obtained are 1) Good teacher observation assessment (73); 2) Good self-assessment (75); 3) Good peer ratings (75).